On the behavioral significance of head direction cells: neural and behavioral dynamics during spatial memory tasks. - Golob, Edward J.; Stackman, Robert W.; Wong, Andrew C. (Behavioral Neuroscience, 2001)
Current theories assume that rats use the directional information reflected by head direction (HD) cells when performing spatial tasks. This assumption was assessed by monitoring anterior thalamic HD cell activity and relating it to the subject's behavioral response on 2 spatial memory tasks that tested either reference memory or working memory. In both tasks, there was a significant number of trials where there was not a tight coupling between the preferred firing direction of HD cells and the direction of the behavioral response. In addition, it was possible to intentionally change the preferred direction of HD cells without affecting performance accuracy. An additional experiment showed that manipulations that affected internal, but not external, cues impaired performance on the reference memory task. These findings suggest that HD cell activity was not consistently guiding the subjects' behavior on these 2 spatial tasks. Reprinted by permission of the publisher.